2021
DOI: 10.1038/s41408-021-00495-3
|View full text |Cite
|
Sign up to set email alerts
|

FLT3 mutated acute myeloid leukemia: 2021 treatment algorithm

Abstract: Approximately 30% of patients with newly diagnosed acute myeloid leukemia (AML) harbor mutations in the fms-like tyrosine kinase 3 (FLT3) gene. While the adverse prognostic impact of FLT3-ITDmut in AML has been clearly proven, the prognostic significance of FLT3-TKDmut remains speculative. Current guidelines recommend rapid molecular testing for FLT3mut at diagnosis and earlier incorporation of targeted agents to achieve deeper remissions and early consideration for allogeneic stem cell transplant (ASCT). Moun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 73 publications
1
74
0
Order By: Relevance
“…An FLT3 -ITD low allelic ratio is not as favorable as the FLT3 -ITD wild-type in patients with AML and NPM1 mutations, as seen previously. Allogeneic HCT for post-remission therapy may be considered to reduce the relapse risk even in patients with FLT3 -ITD low allelic ratio, regardless of NPM1 mutation status [ 12 , 26 - 28 ].…”
Section: Prognostic Significance Of Flt3 -Itd In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…An FLT3 -ITD low allelic ratio is not as favorable as the FLT3 -ITD wild-type in patients with AML and NPM1 mutations, as seen previously. Allogeneic HCT for post-remission therapy may be considered to reduce the relapse risk even in patients with FLT3 -ITD low allelic ratio, regardless of NPM1 mutation status [ 12 , 26 - 28 ].…”
Section: Prognostic Significance Of Flt3 -Itd In Amlmentioning
confidence: 99%
“…Since 1996, when the FLT3 internal tandem duplication (ITD) mutation was first identified in AML, numerous studies have been conducted regarding its relevance in prognosis [ 4 - 6 ]. Moreover, several advances have been made in targeting FLT3 mutations, and currently, FLT3 inhibitors are actively used in clinical practice [ 7 - 12 ]. In this review, we summarize information on clinically available FLT3 inhibitors for the management of AML with FLT3 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors including genetic alterations, chemical exposure, and radiation have been implicated as risk factors of AML [ 1 ]. Among the genetic factors, FLT3-ITD, an internal tandem duplications (ITD) in fms-like tyrosine kinase 3 (FLT3), is observed in approximately 20–30% of AML patients and is associated with aggressive disease progression, worse prognosis, high risk of relapse, and shorter overall survival [ 3 ]. Recent studies showed that somatic mutations at isocitrate dehydrogenases (IDHs) could also drive the development of AML due to the production of oncometabolite 2-hydroxyglutarate (2-HG) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 . Standard dose venetoclax (400 mg/day or dose reduced in accordance with the US label for patients on strong CYP34A inhibitors) was administered starting from day 1 to day 14 or day 28 (depending on the specific clinical trial the patient was enrolled in, or physician choice in off protocol cases) in patients who received triplet therapy, as previously described by our group[ 2 ] (see detailed treatment schema in Supplementary Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Internal tandem duplication (ITD) and tyrosine kinase domain (TKD) mutations in the FLT3 gene are some of the most common mutations in patients with newly diagnosed acute myeloid leukemia (AML). FLT3- ITD mutations are associated with a higher risk of relapse and inferior overall survival (OS) [ 1 , 2 ]. Midostaurin, a first-generation FLT3 inhibitor, combined with intensive chemotherapy, improved OS in younger adult patients (<60 years) with FLT3 mutated AML [ 3 ].…”
Section: Introductionmentioning
confidence: 99%